Metronidazole in prevention and treatment of bacteroides infections in elective colonic surgery. Issue 6061 (5th March 1977) - Willis, A T; Ferguson, I R; Jones, P H; Phillips, K D; Tearle, P V; Fiddian, R V; Graham, D F; Harland, D H; Hughes, D F; Knight, D; Mee, W M; Pashby, N; et al.
Abstract : A double-blind randomised trial was carried out among 46 patients undergoing elective colonic surgery; 27 patients received prophylactic metronidazole and 19 received placebo. Anaerobic infections did not develop in any of the metronidazole-treated patients, but did develop in 11 (58%) of 19 controls who were subsequently successfully treated with metronidazole.